Severe acute disseminated encephalomyelitis complicating measles infection - Morrison, Hamish Duncan (BMJ Case Rep, 2020)
A 36-year-old man presented with an acute progressive encephalopathy, followed by tetraparesis and was diagnosed with acute disseminated encephalomyelitis (ADEM) complicating infection with measles virus. Despite demonstrating a typical rash and other early symptoms of measles infection, there was uncertainty around the initial diagnosis. Cerebrospinal fluid analysis and MRI of the brain and spinal cord were consistent with severe ADEM. He required treatment on intensive care but responded favourably to immunosuppressive therapy. This case highlights the importance of recognising acute measles infection, familiarity with the neurological complications and the potential for good outcome. Healthcare professionals must continue to play an active role in educating the public on the importance of maintaining herd immunity through universal immunisation.